علاقة الرياضة المدرسية بدافعية التعلم والصحة النفسية لدى المتعلمين - مخلوفي, اسعيد (جامعة الوادي - University of Eloued, 2023)
المتعلم هو أساس العملية التربوية كلها، وهو من يتحمل نجاحها أو فشلها، فهو أهم ركن فيها إذا لاقى الرعاية والاهتمام اللازمين لتحقيق أهدافه، وفي مقدمتها إشباع جميع حاجاته النفسية الحركية والعقلية، فالرياضة المدرسية بشكل عام والتربية البدنية بشكل خاص هي الميدان الأنسب لإبراز قدراته ومهاراته ورغباته المختلفة، وبإشباعها تُحرك دافعية التعلم الداخلية والخارجية نحو تحقيق أفضل النتائج العلمية، مما يؤدي إلى توازن وتكيف في الصحة النفسية مع ذاته وأسرته ومع أقرانه من أساتذة ومشرفين تربويين، وعليه يحاول هذا البحث الكشف عن دور الرياضة المدرسية في إثارة الدافعية للتعلم وتحقيق توازن على مستوى الصحة النفسية بإتباع المنهج الوصفي التحليلي المناسب لذلك.The learner is the basis of the whole educational process, and he is the one who can afford to succeed or fail it. He is the most important pillar of the process if he receives the care and attention necessary to achieve his objectives, Foremost among them is the satisfaction of all of his psychological, motor and mental needs, School sports in general and physical education in particular are the fields best suited to demonstrate their different abilities, skills and desires, As a result of the drive of internal and external learning towards the best scientific results, This leads to a balance and adjustment in mental health for himself, his family and his teachers and educators, This research therefore attempts to uncover the role of school sports in stimulating learning and achieving a mental health balance by following the appropriate analytical descriptive curriculum.
School Sports Relationship with Learning Motivation And Mental Health among Learners
مقال
Keywords: الرياضة المدرسية، دافعية التعلم، الصحة النفسية، التلميذ المتمدرس.; School sports, education motivation, psychological health, schoolboy